Pap Smear Versus Colposcopy For Diagnosis Of Precancerous Lesions Of Cervix - Devendra, Kurre Amarawatin, Bariha Kalpana, Sharma Anju, Chaturvedi Hina, Agrawal Megha, Baniwal (International Journal of Scientific Research and Management (IJSRM), 2016)
Background: Cervical cancer presents as major cause of morbidity and mortality especially in developing countries like India. Various screening programs are implemented for its early detection and treatment, which makes it imperative to have a reliable screening investigation for wider application.Objective :  TO evaluate the role of  Colposcopy  and Pap smear and compare their efficacy for diagnosis of  preinvasive cervical lesions.Material and Methods : This hospital based   prospective study was conducted  in SMS Medical College, Jaipur  in 35 patients from 2013 to 2014. All patient subjected to  Pap smear and Colposcopy. The sensitivity, specificity, and accuracy were calculated for  Pap smear and  Colposcopy.Results : sensitivity of colposcopy was 88%% and specificity was  70%, while Sensitivity of  conventional pap smear (Bethesda system)60%,Specificity 84%.colposcopy use as screening method   has  higher chance of detecting  precancerous lesions.Conclusion : colposcopy is useful as better  screening method  in  compare with  conventional  pap smear detecting premalignant and malignant lesions of the cervix.